(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The objective of this study was to evaluate the analgesic potential of Caesalpinia bonducella L (Roxb.) by evaluating the efficacy of leaf and stem bark extracts and isolated nutraceuticals. Nutraceuticals were isolated via column chromatography and characterized using IR and NMR. Analgesic activities were assessed in vivo using the hot plate, capsaicin-induced pain, and tail flick tests on 36 albino mice across nine groups. Phytochemical screening revealed flavonoids and polyphenols. Pure nutraceuticals displayed superior analgesic properties compared to the control. Ethanol extracts of Caesalpinia bonducella leaf and bark exhibited higher analgesic efficacy than other extracts and the control (P<0.05). The study suggests the plant's potential in the nutraceutical field, highlighting its therapeutic value and positioning it as a valuable resource for India's nutraceutical sector.